Debating Ethics in HIV Research: Gaps between Policy and Practice in Nigeria. Issue 3 (27th June 2014) - Folayan, Morenike Oluwatoyin; Peterson, Kristin; Haire, Bridget; Brown, Brandon; Audu, Kadiri; Makanjuola, Olumide; Pelemo, Babatunde; Marsh, Vicki
Abstract: HIV prevention is a critical health issue in Nigeria; a country that has one of the worst HIV epidemic profiles in the world. With 270, 000 new infections in 2012, Nigeria is a prime site for HIV prevention research. One effect of the HIV epidemic has been to revolutionalise ethical norms for the conduct of research: it is now considered unethical to design and implement HIV related studies without community engagement. Unfortunately, there is very little commensurate effort in building the capacity of local persons to engage actively with researchers, and there is no existing platform to facilitate dialogue between researchers and communities engaged in research in Nigeria. In an effort to address this gap, we undertook a series of three community dialogues (Phase One) and two community‐researcher interface meetings (Phase Two) in Nigeria. This paper aims to give an empirical account of the dialogue from these community engagement processes and provide a resulting critique of the implementation of research ethics practices in Nigeria. It is anticipated that the outputs will: (i) support researchers in designing community‐based research protocols; (ii) inform ethics committees of key considerations during research protocol reviews from a community perspective; and (iii) inform policy makers and research sponsors about issues of primary concern to communities with respect to HIV research.